2021
DOI: 10.1089/pop.2019.0196
|View full text |Cite
|
Sign up to set email alerts
|

Population-Level Reach of Cardiovascular Disease Prevention Interventions in a Rural Community: Findings from the Heart of New Ulm Project

Abstract: This study examines participation by residents of a rural community in programs implemented as part of The Heart of New Ulm (HONU) Project, a population-based cardiovascular disease (CVD) prevention initiative. The study compares participation rates for the various interventions to assess which were the most engaging in the priority community and identifies factors that differentiate participants vs. nonparticipants. Participation data were merged with electronic health record (EHR) data representing the large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…PHC teams should therefore continue to use low-cost, practical approaches to detect people at risk [ 61 ]. On the other hand, previous research also demonstrates that relatively high levels of community engagement can be attained by introducing community-based CVD prevention programs [ 62 ], and that it has the potential to effectively reach under-served groups [ 63 ]. Community-based strategies previously have successfully led to an improvement in CVD risk factors [ 64 ], with especially positive impact on improving population knowledge on CVD and risk factors, physical activity levels, and dietary patterns [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…PHC teams should therefore continue to use low-cost, practical approaches to detect people at risk [ 61 ]. On the other hand, previous research also demonstrates that relatively high levels of community engagement can be attained by introducing community-based CVD prevention programs [ 62 ], and that it has the potential to effectively reach under-served groups [ 63 ]. Community-based strategies previously have successfully led to an improvement in CVD risk factors [ 64 ], with especially positive impact on improving population knowledge on CVD and risk factors, physical activity levels, and dietary patterns [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“… RCT, randomized controlled trial; Sig, statistically significant; NM, not measured; CVD, cardiovascular disease; LDL-C, low-density-lipoprotein cholesterol; BMI, body mass index; DM, diabetes mellitus; PMA, Panel Management Assistants; FRS, Framingham Risk Score. a Interventions with separate studies in which additional information was found: 1 Sidebottom et al, 2016 ( 39 ), Sidebottom et al, 2021 ( 21 ); 2 Lewinski et al, 2021 ( 40 ); 3 Jiao et al, 2014 ( 41 ); 4 Strauss et al, 2015 ( 42 ); 5 Smith et al, 2019 ( 43 ). …”
Section: Resultsmentioning
confidence: 99%
“…In order to improve reach in future program planning and development, literature indeed recommends the integration of health and social care for vulnerable populations through multisectoral and community-based strategies (Richard et al, 2016;Corscadden et al, 2018). Previous studies have shown that this has great potential to increase community engagement levels and the reach of currently under-served populations, resulting in a positive impact on cardiovascular disease and its risk factors (Woringer et al, 2017;Sidebottom et al, 2021;Soltani et al, 2021).…”
Section: Discussionmentioning
confidence: 99%